The Influence of Firm Characteristics on Corporate Social Responsibility and Its Impact on Stock Prices - Linda A.O. Tanor (Journal of International Conference Proceedings (JICP), 2018)
There is a reciprocal relationship between the company and the community as its external environment. Therefore, the existence of the company cannot be separated from the community. From an economic aspect, companies must be profit-oriented and from the social aspect, the company must contribute directly to the community. Thus, the company is not only faced with responsibility in obtaining profits, but also must pay attention to its social and environmental responsibilities. This study aims to examine the influence of company characteristics including Profitability, Leverage, Managerial Ownership, Company Size on Disclosure of Corporate Social Responsibility (CSR) and the impact of CSR Disclosures on Stock Prices. This study was conducted on companies listed on the Indonesia Stock Exchange in the 2014-2016 period. The sample selection procedure is done by using purposive sampling method and the results are 14 companies that meet the criteria. The analysis technique that will be used is a two-stage regression analysis. The results of testing hypotheses show that the characteristics of the company that are proven to have an effect on CSR disclosure include: profitability and firm size while leverage and managerial ownership are not proven to influence CSR disclosure. Other findings indicate that CSR disclosure affects stock prices as measured by abnormal returns. This finding proves that if the company has good environmental and social performance, investors will respond positively through an increase in stock prices. Keywords: firm characteristic, Corporate Social Responsibility, stock price.